2022
DOI: 10.31234/osf.io/g6s8f
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Well-Being in Social Interactions: Examining Personality-Situation Dynamics in Face-to-Face and Computer-Mediated Communication

Abstract: Decades of research show that people’s social lives are linked to their well-being. Yet, research on the relationships between social interactions and well-being has been largely inconclusive with regard to the effects of person-situation interactions, such as the interplay between contextual factors (e.g., interactions occurring in physical vs. digital contexts, different interaction partners) and dispositional tendencies (e.g., Big Five personality traits). Here, we report on exploratory and confirmatory fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…In addition to studies investigating different leisure activities simultaneously, large literatures exist about specific activities. For instance, more frequent social interactions have been associated with higher well-being (e.g., Kroencke et al, 2022; Lucas et al, 2008; Sun et al, 2020). Similarly, physical activity is positively associated with well-being between persons (e.g., Buecker et al, 2021; Kroencke et al, 2019; Wiese et al, 2018).…”
Section: Conceptualizing Leisure Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to studies investigating different leisure activities simultaneously, large literatures exist about specific activities. For instance, more frequent social interactions have been associated with higher well-being (e.g., Kroencke et al, 2022; Lucas et al, 2008; Sun et al, 2020). Similarly, physical activity is positively associated with well-being between persons (e.g., Buecker et al, 2021; Kroencke et al, 2019; Wiese et al, 2018).…”
Section: Conceptualizing Leisure Activitiesmentioning
confidence: 99%
“…Other work has focused on specific leisure activities at the within-person level. For instance, many studies indicate momentary well-being benefits of social interactions (e.g., Kroencke et al, 2022; Sun et al, 2020) and positive effects of social leisure on life satisfaction were also reported at larger timescales (e.g., Becchetti et al, 2012). Physical activity has been related to momentary (Liao et al, 2015), weekly (Kroencke et al, 2019), and biennial fluctuations in well-being (Perales et al, 2014), and similar effects were evident in experimental designs (Buecker et al, 2021).…”
Section: Conceptualizing Leisure Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many areas of inquiry focus on individual differences in contingencies. For instance, research on stress reactivity has examined individual differences in affective reactivity towards stressors (e.g., Hisler et al, 2020;Kaurin et al, 2021;Kroencke et al, 2020;O'Neill et al, 2004); research on motivation has examined individual differences in the associations between need satisfaction and well-being (e.g., Neubauer et al, 2018Neubauer et al, , 2020b; and work on the association between Extraversion and well-being has examined the social reactivity hypothesis (Srivastava et al, 2008;Kroencke et al, 2022). Moreover, research on contingencies has been conducted in various applied areas of psychology.…”
Section: Previous Empirical Work On Contingenciesmentioning
confidence: 99%
“…Many areas of inquiry focus on individual differences in contingencies. For instance, research on stress reactivity has examined individual differences in affective reactivity towards stressors (e.g., Hisler et al, 2020; Kaurin et al, 2021; Kroencke et al, 2020; O’Neill et al, 2004); research on motivation has examined individual differences in the associations between need satisfaction and well-being (e.g., Neubauer et al, 2018; Neubauer, Lerche, et al, 2020); and work on the association between Extraversion and well-being has examined the social reactivity hypothesis (Kroencke et al, 2022; Srivastava et al, 2008). Moreover, research on contingencies has been conducted in various applied areas of psychology.…”
Section: Introductionmentioning
confidence: 99%